Material aspects of reading in ancient and medieval cultures: materiality, presence and performance - Krauß, Anna H.; Leipziger, Jonas; Schücking-Jungblut, Friederike (Materiale Textkulturen, 2020)
Frontmatter -- Acknowledgements -- Contents -- Material Aspects of Reading and Material Text Cultures -- Material Aspects of Rituals Beyond Their Instructions -- Scribal Production and Literacy at Qumran -- Scribal Habits and Scholarly Texts -- Reading Psalm and Prayer Manuscripts From Qumran -- Reading the Songs of the Sabbath Sacrifice -- Reading Material Features of Qumran Tefillin and Mezuzot -- Reading an Opisthograph at Qumran -- Codices des Typs C und die Anfänge des Blätterns -- Ancient Jewish Greek Practices of Reading and Their Material Aspects -- Reading Early New Testament Manuscripts -- What Ancient Christian Manuscripts Reveal About Reading (and About Non-Reading) -- Reading Regularly -- Encountering the Grotesque -- Notes on Contributors -- Indices